Prevalence and association of welding related systemic and respiratory symptoms in welders. Issue 9 (22nd August 2003) - El-Zein, M; Malo, J-L; Infante-Rivard, C; Gautrin, D
Abstract : Background: The prevalence of welding related respiratory symptoms coexisting with welding related systemic symptoms in welders is unknown. Aims: To determine in a sample of welders the prevalence of coexisting welding related systemic symptoms indicative of metal fume fever (MFF) and welding related respiratory symptoms suggestive of occupational asthma (OA), and the strength and significance of any association between these two groups of symptoms. Methods: A respiratory symptoms questionnaire, a systemic symptoms questionnaire, and a questionnaire on occupational history were administered by telephone to 351 of a sample of 441 welders (79.6%) from two cities in Québec, Canada. Results: The co-occurrence of possible MFF (defined as having at least two symptoms of fever, feelings of flu, general malaise, chills, dry cough, metallic taste, and shortness of breath, occurring at the beginning of the working week, 3–10 hours after exposure to welding fumes) together with welding related respiratory symptoms suggestive of OA (defined as having at least two welding related symptoms of cough, wheezing, and chest tightness) was 5.8%. These two groups of symptoms were significantly associated (χ 2 = 18.9, p < 0.001). Conclusion: There is a strong association between welding related MFF and welding related respiratory symptoms suggestive of OA. As such, MFF could be viewed as a pre-marker of welding related OA, a hypothesis that requires further investigation.